Globalization and the rise of integrated world society: deterritorialization, structural power, and the endogenization of international society. Issue 3 (November 2019) - Babones, Salvatore; Aberg, John H. S.
Abstract: There is a widespread feeling that globalization represents a major system change that has or should have brought world society to the forefront of international relations theory. Nonetheless, world society remains an amorphous and undertheorized concept, and its potential role in shaping the structure of the international society of states has scarcely been raised. We build on Buzan's (2018, 2) master concept of 'integrated' world society ('a label to describe the merger of world and interstate society') to locate the integration of world society in the globalization of social networks. Following the advice of Buzan (2001) and Williams (2014), we use conceptual frameworks from international political economy to systematically explore the structure of integrated world society along six dimensions derived from Mann (1986) and Strange (1988): military/security, political, economic/production, credit, knowledge, and ideological. Our empirical survey suggests that, on each of these dimensions, power has centralized as it has globalized, generating steep global hierarchies in world society that are similar to those that characterize national societies. The centrality of the United States in the networks of world society makes it in effect the 'central state' of a new kind of international society that is endogenized within integrated world society.